Author Correction: Comparison of DNA-, PMA-, and RNA-based 16S rRNA Illumina sequencing for detection of live bacteria in water. Issue 1 (December 2018) - Li, Ru; Tun, Hein; Jahan, Musarrat; Zhang, Zhengxiao; Kumar, Ayush; Dilantha Fernando, W.; Farenhorst, Annemieke; Khafipour, Ehsan
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.